Climate change influence water use pattern in south-west coastal belt of Bangladesh - Tusar, KD; Moumita, C (Journal of Environmental Science and Natural Resources, 2015)
The southwest part of the coastal area in Bangladesh is to be identified as environmental handicap by both climate change and non-climatic drivers. The water resource sector of the coastal region would most likely be affected significantly due to anticipated changes. The research tries to identify the present status and probable impacts of climate change on changing water use scenario in the transition zone of fresh water and brackish water. Necessary data were collected through questionnaire survey and Focus Group Discussions (FGD) in December, 2012. A total of 100 households were surveyed in the presence of both male and female from five types of drinking water source user namely Protected pond, Pond Sand Filter, Rainwater harvesting, Tube well and Supply water.The survey was conducted to 30 up age group and equal numbers of respondents were selected from each source user. About 49% of peoples are literate and 29% of people are engaged in open water fishing in the Sunderbans. During monsoon 87% of people use rain water for drinking purpose while in other seasons of the year they use pond sand filter and protected pond water while before Aila, Sidr 51% people were use protected pond water. In 90% of household women involved drinking water collection and 65% of households directly consume water from sources. About 80% of households use rain water for cooking in monsoon and 60% of households use pond water in others seasons of the year. Most of the households use pond water for bathing, washing, sanitary purpose, irrigation, fish cultivation and fish processing but most of them use river water for shrimp cultivation. Except rain water harvesting and water supply system most of the water sources in the coastal region were affected by natural disaster at different levels. This study will helps policy makers to find out alternative water source for coastal people. DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22122 J. Environ. Sci. & Natural Resources, 6(2): 217-225 2013